CONTRIBUTION OF THE ORGANIC WASTE FROM FISH CULTURE ON THE DEGRADATION OF WATER QUALITY OF RESERVOIR CIRATA - Soetrisno, Yudhi (Jurnal Teknologi Lingkungan, 2006)
Cirata is one of three reservoirs lay in Citarum River, where the waterbody is used to fish culture in floating net. Lately, one or two times in ayear, fish in the floating n die massly because of the water quality ofet reservoirs have worsen, which resulted from the entering of organicpollutant from human being activities in and outside of the Reservoir. Thispaper is written to reveal contribution of organic waste from fish culture infloating net represented human being activities inside of the Reservoir onthe worsening of water quality Cirata. The result revealed that theReservoir Cirata continually has been polluted by organic waste, whichgradually resulted in the worsening of water quality indicated byincreasing chemical oxygen demand (COD) and concentration ofchlorophyll-a (Chl-a), and decreasing secchi disk. This study indicatedthat on 1997, fish culture using floating net (internal loading) in ReservoirCirata contribute the nutrient three times than domestic and agriculture(external loading). This situation is guessed still going on hitherto,therefore the reservoir become very hypertrophic, as giant cesspools, andresulted in death of fish massly.